The Evil Eye in The Sermon on the Mount - Wheeler, Ronald E. (Stone-Campbell journal, 2001)
Jesus reference to the evil eye in the Sermon on the Mount has proved difficult for generations of commentators. Recent efforts, including social-scientific approaches, have advanced our understanding of the passage. This article includes a review of what the various approaches have done with the passage, and an attempt to advance the discussion through a literary-critical approach. The literary approach should complement the previous approaches and enhance understanding of the saying.